2004
DOI: 10.1111/j.1460-9568.2004.03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic innervation of striatal and subthalamic neurons projecting to the rat entopeduncular nucleus

Abstract: The present study analyses the anatomical arrangement of the projections linking the Wistar rat parafascicular thalamic nucleus (PF) and basal ganglia structures, such as the striatum and the subthalamic nucleus (STN), by using neuroanatomical tract-tracing techniques. Both the thalamostriatal and the striato-entopeduncular projections were topographically organized, and several areas of overlap between identi®ed circuits were noticed, sustaining the existence of up to three separated channels within the Nauta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 78 publications
1
61
1
Order By: Relevance
“…Both direct and indirect pathway MSNs have been shown to receive synaptic input from the cortex (Somogyi et al, 1981;Hersch et al, 1995;Lei et al, 2004). Light microscopic studies have suggested that the same is true for thalamostriatal afferents (Lanciego et al, 2004;Castle et al, 2005). Electron microscopic studies in primates have suggested that afferents from the centromedian nucleus (CM) of the thalamus preferentially innervate direct pathway MSNs (Sidibé and Smith, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…Both direct and indirect pathway MSNs have been shown to receive synaptic input from the cortex (Somogyi et al, 1981;Hersch et al, 1995;Lei et al, 2004). Light microscopic studies have suggested that the same is true for thalamostriatal afferents (Lanciego et al, 2004;Castle et al, 2005). Electron microscopic studies in primates have suggested that afferents from the centromedian nucleus (CM) of the thalamus preferentially innervate direct pathway MSNs (Sidibé and Smith, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…The centromedian-parafascicular thalamic complex (CM-Pf) is one major source of glutamatergic innervation of several basal ganglia nuclei, including the striatum, 1-15 the subthalamic nucleus (STN), 4,7,[12][13][14][15][16][17][18][19][20][21] the globus pallidus, and the substantia nigra. 15,21,22 Projections arising from the caudal intralaminar nuclei are excitatory and use glutamate as neurotransmitter.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Such functional differences are consistent with forebrain control of energy homeostasis in which a fall in O 2 availability triggers a transduction cascade involving activation of 5=-nucleotidase, formation of ADO, stimulation of A 2A receptors, and excitation of Pf neurons that depress respiration (40,42,44). Activity of Pf neurons is reflected in changes in expression of molecular intermediates in mitochondrial O 2 consumption and other elements and pathways of cellular energetics (4,31,51,63,75). These advances now enable the study of molecular components of Pf related to neuronal activation and control of energy metabolism.…”
Section: Physiological Implicationsmentioning
confidence: 72%
“…This derived primarily from early recognition of degeneration of substantia nigra neurons (79), its role in Parkinson's disease (4,31,33,75), and evidence of its segregated striatal projections (51,84,85,88,94), as well as widespread interest in recognition of its distinctive role in metabolic regulation (4,33,51,63,75,94). The classification of Pf together with the centre median nucleus as part of the intralaminar group (8) or the "postmedial group" proposed by Rose (69) shall presumably rely upon recent findings now emerging from identification of molecular components and their regulators in conserving the energetics that sustain respiration and tissue oxygenation (75,76).…”
Section: Thalamic Pf and Hypoxic Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation